RELEVANSI METODE PENDIDIKAN ISLAM DI TENGAH ARUS DIGITALISASI GLOBAL - Zaleha, Siti; Muharrani (STIT Hamzah Al Fansuri, 2025)
The development of information and communication technology has brought the world into an era of global digitalization that affects various aspects of life, including education. Islamic education as a system that emphasizes the formation of morals, spirituality, and intellectuality, faces challenges as well as opportunities in the ever-growing digital flow. This study uses a qualitative descriptive approach with a literature review method. Data collection was carried out by collecting and analyzing various relevant scientific sources, including journals, books, and academic articles. The results of this study indicate that 1) The relevance of Islamic education methods in the digital era is highly dependent on the ability to adapt and innovate in order to remain effective and in accordance with the times. 2) Synergy is needed between technology and Islamic values ​​so that Islamic education remains alive, contextual, and effective